A SYNTACTICAL ANALYSIS OF HEADLINE EDUCATION TOPIC NEWS ON THE CNA WEBSITE - Zulhakim, Muthiah Khairunisa; Haqiqi Ma’mun, Akhmad (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Syntax aims to the rules and procedures that are used in certain languages to put together sentences. Learning syntax is essential because it enables us to illustrate the structures of sentences more clearly and efficiently and to look into the structure of English sentences. In reality, many readers and writers have poor comprehension of sentence structure, particularly the structure of sentences written in English. This problem is also encountered by students of English education who are enrolled in classes that cover information related to syntax, as well as by other readers who are not familiar with the role of syntax in sentence structure or how to draw tree diagrams by Noam Chomsky's theory. This study intends to answer the following questions: (1) What various types of sentences on education headline news from the CNA website from January 1–31, 2023 to February 27-2023? (2) How are the sentences in education headline news from the CNA website from January 1–31, 2023 to February 27-2023 generated in tree diagrams? The method of qualitative research known as "descriptive research" was utilized for this study. As a result of this research, The types of sentences that are utilized include simple sentences, compound sentences, and complex sentences.